Changes to local area public sector spending and food purchasing in England: a longitudinal ecological study. Issue 1 (4th March 2022) - Jenkins, Rosemary H; Vamos, Eszter P; Taylor-Robinson, David; Mason, Kate E; Laverty, Anthony A
Abstract : Objectives: Changes in public sector service spending may influence food consumption. We make use of changing local authority (LA) expenditure in England to assess impacts on food purchasing. We examine total LA service spending and explore two potential pathways: highways and transport spending which may affect access to food; and housing service expenditure which may affect household resources available to purchase foods. Design: Longitudinal panel survey at the LA level (2008–2015) using fixed effects linear regression. Setting: 324 LAs in England. Main exposure: Expenditure per capita on total LA services, highways and transport services, and housing services. Main outcome measures: LA area estimates of purchasing of fresh fruits and vegetables, high in fat, sugar and salt (HFSS) foods, and takeaways at home, expressed as a percentage of total food and drink expenditure. Results: Total LA service spending decreased by 17% on average between 2008 and 2015. A 10% decrease in total LA spending was associated with a 0.071 percentage point decrease in HFSS (95% CI −0.093 to –0.050) and a 0.015 percentage point increase in takeaways (95% CI 0.006 to 0.024). A 10% decrease in highways and transport expenditure was associated with a 0.006 percentage point decrease in fruit and vegetable purchasing (95% CI −0.009 to –0.002) and a 0.006 percentage point increase in takeaway purchasing (95% CI 0.001 to 0.010). These associations were seen in urban areas only when analyses were stratified by rural/urban area status. A 0.006 percentage point decrease in HFSS purchasing was also seen with a 10% decrease in housing expenditure (95% CI −0.010 to –0.002). Conclusion: Changes in LA spending may have impacts on food purchasing which are evident at the area level. This suggests that in addition to more prominent impacts such as foodbank use, austerity measures may have mixed impacts on food purchasing behaviours among the wider population. Individual-level research is needed to further elucidate these relationships.